Pengaruh Video Marketing, Live Streaming dan Integrasi Nilai–Nilai Pancasila Terhadap Peningkatan Penjualan Kainranah di Platform Tiktok - Mila Karina; Nur Indah Sari; Sabrina Gea Putri Gandhi; Restu Pangestu (Yayasan Darussalam Bengkulu, 2024)
This study explores the effectiveness of video marketing, live streaming, and the integration of Pancasila values ​​in increasing Kainranah sales on TikTok. This research reveals how attractive marketing strategies and direct interaction with consumers, as well as an emphasis on Pancasila values ​​such as togetherness and social justice, can increase brand awareness, consumer interest and sales. Targeting consumers aged 25-35 years, Kainranah's popular products related to pregnancy and childbirth, especially Kimonos, were analyzed using descriptive and quantitative methods. The study results show that the combination of video marketing, live streaming, and the application of Pancasila values ​​can create interactive experiences, build trust, and increase purchasing interest through incentives and social awareness. This strategy has proven to be the key to Kainranah's marketing success on the TikTok platform.